KEBIJAKAN PEMERINTAH PROVINSI BALI DALAM PENYELENGGARAAN PARIWISATA DIGITAL BUDAYA BALI - Cokorde Istri Dian Laksmi Dewi (Jurnal AKSES, 2021)
The Covid-19 pandemic has had implications for the decline in the number of tourist visits. In response to this, the government introduced a digital tourism policy. This policy is also followed by the Provincial Government of Bali. This study will discuss the basic legal policies of the Bali Provincial Government in the implementation of digital tourism and the scope of digital tourism policies. This research is a normative juridical research, especially in reviewing the Bali Provincial Regulation Number 5 of 2020 concerning Standards for the Implementation of Balinese Cultural Tourism. The basic legal policies of the Bali Provincial Government in implementing digital tourism are carried out in series with regional autonomy. The implementation of digital tourism for Balinese culture includes tourism inspiration; tourist arrivals; Tourism destinations and activities; post-visit tourist treatment; Bali Tourism One Stop Portal; and digital documentation of Balinese Cultural Tourism. Sociologically, this policy is based on the declining condition of Bali tourism, but on the other hand there is an increase in the use of information technology.